1976
DOI: 10.1289/ehp.7614103
|View full text |Cite
|
Sign up to set email alerts
|

Control and management of insect populations by chemosterilants.

Abstract: Chemosterilants, i.e., chemical compounds that interfere with the reproduction potential of sexually reproducing organisms, can be used in three new approaches to insect control. In the sterile-insect release technique, the principal problem is to develop compounds and methods for their application that would not result in introducing harmful residues into the environment. Because of the unusual and often unique circumstances connected with releasing large numbers of sterilized insects, the residue problem and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
0
16
0
2
Order By: Relevance
“…In ancient China, the crude extract of Camptotheca acuminate containing CPT has been used traditionally to control insect pests for centuries, and it was reported to be a potent chemosterilant against the housefly and cabbage caterpillar . It also exhibited significant inhibitory activities against several agricultural pests such as Empoasca vitis, Mythimna separate Walker, Brevicoryne brassicae , Nilaparvata lugens , and Chilo suppressalis , supporting its potential use as a field pesticide . Additionally, a recent study showed that CPT could cause visible changes in the midguts from the lepidopteran pests Trichoplusia ni and Spodoptera exigua , such as losing the single layer of epithelial cells and disrupting the peritrophicmembrane .…”
Section: Biological Activity Of Cpt and Related Derivativesmentioning
confidence: 99%
“…In ancient China, the crude extract of Camptotheca acuminate containing CPT has been used traditionally to control insect pests for centuries, and it was reported to be a potent chemosterilant against the housefly and cabbage caterpillar . It also exhibited significant inhibitory activities against several agricultural pests such as Empoasca vitis, Mythimna separate Walker, Brevicoryne brassicae , Nilaparvata lugens , and Chilo suppressalis , supporting its potential use as a field pesticide . Additionally, a recent study showed that CPT could cause visible changes in the midguts from the lepidopteran pests Trichoplusia ni and Spodoptera exigua , such as losing the single layer of epithelial cells and disrupting the peritrophicmembrane .…”
Section: Biological Activity Of Cpt and Related Derivativesmentioning
confidence: 99%
“…[33] In a field trial in Southern Mississippi following a single integrated insecticide and SIT application, the boll weevil population in the eradication zone was suppressed below detectable levels in 203 out of 246 fields, [3] with an estimated chemical release of 100 ng busulfan/weevil or 6 mg per square mile. [34] …”
Section: Non-alkylating Dimethylamines Non-aziridine Alkylating Amentioning
confidence: 99%
“…In the early 1970s the development of diflubenzuron ( 18 ) or Dimilin® (TH 6040), marked a new class of insecticides, the benzoylphenyl ureas. [34,52] Diflubenzuron has low toxicity (LD 50 >2000 mg/kg, no genotoxic or reproductive toxicity observed), although hemotoxicity is noted upon chronic administration at 2 mg/kg. [47a] However, diflubenzuron displays significant toxicity towards marine invertebrates, [53] so it is not suitable for dissemination in aquatic habitats.…”
Section: Chitinase Inihibitorsmentioning
confidence: 99%
“…Camptothecin (CPT) (Fig. 1), an indole alkaloid, was first isolated from extracts of C. acuminate by Wall and Wani in 1958 and was reported to be a potent chemosterilant against the housefly and cabbage caterpillar 6, 7. In China, the crude extract of C. acuminate has been used traditionally to control pests, and it was reported that CPT showed significant biological activities against Empoasca vitis, Brevicoryne brassicae, Nilaparvata lugens and Chilo suppressalis , which suggested its potential use as a pesticide in the field 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…Camptothecin stably binds to the ‘cleavable complex’ topo I‐linked DNA site and acts as a physical barrier to DNA synthesis, resulting in replication fork collision and cell death 20, 21. According to reports, CPT affects insects mainly by interfering with the reproduction potential of sexually reproducing organisms 7. However, little attention has been focused on the relationship between cell proliferation inhibition and apoptosis in insect cell lines after treatment with CPT and its derivatives, which will illustrate the mechanism of CPT action on insects at the molecular and cellular level.…”
Section: Introductionmentioning
confidence: 99%